Rancang Bangun Purwarupa Pendeteksi Kesegaran Ikan Berbasis Ciri Warna Dan Bau - Khalif, Fajar Al; Yudhana, Anton (Fakultas Teknik Universitas Khairun, 2024)
At this time the development of technology is rapid that there are many tools facilitate human work, one of which is to detect the freshness of fish. In Indonesia alone there are many types of fish consumption derived from sea water and fresh water. Fish consumtion in Indonesia increased every year by an average of 3% based on statistics from the Ministry of Fisheries and Marine Affairs from 2014-2019. Â The system designed in this study uses color sensors and odor sensors that serve to detect the freshness of fish. The microcontroller used is arduino nano which serve to process programs that have been designed. The study used TCS-3200 and MQ-135 sensors as inputs that were then processed in the Arduino Nano which was then displayed on the LCD. Tets on this study used catfish as objects. Catfish will be classified into two, namely fresh and not fresh. The worse the quality of the fish, the greater the PPM value. The error rate in this study is quite large at 7,1.